Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41598-022-25317-9
|View full text |Cite
|
Sign up to set email alerts
|

Positive attentional bias mediates the relationship between trait emotional intelligence and trait affect

Abstract: Emotional intelligence and, in particular, the component emotion regulation may increase well-being and improve mood and coping with negative emotions. In the present eye-tracking study, we examined whether attention allocation to positive stimuli mediates the relationship between emotion regulation abilities and trait affect. Gaze behavior of 104 healthy adults was analyzed in a free-viewing task, in which happy, sad, angry, and neutral faces were shown simultaneously for ten seconds. Dwell time on facial exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…También se observa un valor predictivo en ambos estados afectivos. Precisamente, estudios previos (Fernández-Berrocal et al, 2017;Jiménez et al, 2019;Noor et al, 2021;Sánchez-Álvarez et al, 2015;Suslow et al, 2022;Vergara et al, 2015) han mostrado que la Claridad y la Reparación Emocional predicen de forma significativa la AP, la satisfacción con la vida, la autoeficacia y el bienestar psicológico.…”
Section: Discusión Y Conclusionesunclassified
“…También se observa un valor predictivo en ambos estados afectivos. Precisamente, estudios previos (Fernández-Berrocal et al, 2017;Jiménez et al, 2019;Noor et al, 2021;Sánchez-Álvarez et al, 2015;Suslow et al, 2022;Vergara et al, 2015) han mostrado que la Claridad y la Reparación Emocional predicen de forma significativa la AP, la satisfacción con la vida, la autoeficacia y el bienestar psicológico.…”
Section: Discusión Y Conclusionesunclassified
“…In addition, through both webcam-based and remote video eye tracking in three experimental conditions, Wisiecka et al ( 2022 ) found that the time to first fixation toward happy faces was significantly shorter than toward sad faces in face-in-the-crowd (FIC) tasks. Similarly, in a study examining the mediating role of attention to positive faces in the relationship between Trait EI and affect, Suslow et al ( 2022 ) found that emotion regulation was associated with fixation time on happy faces in a free-viewing paradigm where four emotional faces (angry, happy, sad, and neutral) were presented simultaneously.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast to other findings, there were no associations between EI and bias for happy faces. However, it is important to note that Davis ( 2018 ) used a different type of paradigm and assessed early attentional preference compared to sustained attention that was examined by Lea et al ( 2018 ) and Suslow et al ( 2022 ).…”
Section: Introductionmentioning
confidence: 99%